Ongoing Conversation: A New Ignatian Ideal? - Endean, Philip (The way, 2022)
The article explores the Ignatian idea of ongoing conversion through an understanding of God's grace and salvation in the Christian spiritual life. Topics discussed are theology of divine mercy as a source of mission in terms of reconciliation with God, conversion as the fruit of mission that provide spiritual renewal and growth, conversion as a prelude to discernment, Ignatian meditations on sin and grace to attain the love of God and the interplay between conversion and discipleship.